A pessoa idosa no ensino superior público: perfil, motivações e expectativas - Silveira, Clarita Souza Baroni (2020)
The phenomenon of population aging observed in developed countries and also those in development, like Brazil, have defied more and more the public policies in attending the specific demands of his new social actor: the elderly person. Gerontology as an area of scientific knowledge busy with the comprehension of multidimensional factors that dream up human aging has pointed out the necessity of understanding the social determinations of this process even more. Schooling level has assumed the centrality of the discussions in gerontology as an indicator of protection to the elderly. However, in a scenario in which illiteracy takes on narrow bonds with the aging segment we notice discreet but gradual increasing of the aged population in college. Thus, the present study started from the necessity of enlarging the discussion about the entry of elderly people while college students. So, the purpose of this research was described the enrollment situation of elderly students in degree courses at a Federal Institution of Higher Education; to characterize the sociodemographic perfile of elderly students enrolled in degree courses at a Federal Institution of Higher Education; identify the motivations, the challenges and the expectations of the elderly people that joins College, through basic lexicografy. From a qualitative and quantitative approach we have searched for an outline of the situation of the enrollment of the elderly students linked to a federal institution from 2016 to 2019 (population=57). From this survey the students (sample=34) answered to Brazil Old Age Schedule that permitted measuring variables like sex, age, marital status, city of origin, family composure, family income, home situation occupation and scholar studies. The data were stored in a Microsoft Excell® spreadsheet and, later, analyzed by the SPSS® software and presented in a table with mean, standard deviation and median. During the second stage of the research (qualitative) a semi-structured interview was held with some students (n=9) to understand the motives that led to the entrance in college, the challenges faced in academic context and the expectations related to the course chosen. The data were analysed from Software IRAMUTEQ on. The results proved a different profile of the students that were mostly men, ages of 62 that entered by a selective process. Still, a great number had graduation and referred to having satisfaction in life in general. We verified that many students returned to university after retiring, mostly to have a second graduation or to conclude courses started and interrupted, living the academic experience in old ages in a different manner, looking for new knowledge and giving also a new meaning to this time of their lives.